Early medieval settlement in upland Perthshire : excavations at Lair, Glen Shee 2012-17 - Strachan, David, 1966- (Archaeopress Archaeology, 2019)
Archaeological evidence for settlement and land use in early medieval Scottish upland landscapes remains largely undiscovered. This study records only the second excavation of one important and distinctive house form, the Pitcarmicktype building, in the hills of north-east Perth and Kinross. Excavation of seven turf buildings at Lair in Glen Shee has confirmed the introduction of Pitcarmick buildings in the early 7th century AD. Clusters of these at Lair, and elsewhere in the hills, are interpreted as integrated, spatially organised farm complexes comprising byre-houses and outbuildings.